HUBUNGAN AIR DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS TANJUNG AGUNG KABUPATEN MUARA ENIM TAHUN 2023 - Sarnili, Sarnili; Novitry, Fera; Sarwoko, Sabtian; Maulana, Muchsin (Universitas Ahmad Dahlan, 2024)
Stunting is one of the many nutritional problems encountered in Indonesia. WHO data (2020), more than half a percent globally of children under 5 years of age are stunted in the Asian Region with the highest stunting case rate of 53%, followed by the African Region with 41%. Indonesia is still included in the category of very high stunting cases with a percentage of 31.8%. Tanjung Agung Health Center ranks 2nd with the most cases of stunting in 2022. Tanjung Agung Village is a village where there are quite a number of stunting locations because for 2 consecutive years the percentage of stunting can be said to have increased, namely in 2021 there were 5.54% cases and 2022 by 21%. The research design used in this research is observational analytic using quantitative data through a cross sectional approach. The population in this study were toddlers aged 6-24 months in Tanjung Agung, Pagar Dewa and Paduraksa villages totaling 195 toddlers. The sample in this study were toddlers who lived in Tanjung Agung Village, Pagar Dewa and Paduraksa Village. Based on univariate analysis, it was found that out of 130 respondents, 41 (31.5%) experienced stunting compared to 89 (68.5%) who were not stunted. Based on the condition of clean water, it is known that out of 130 respondents, it was found that those who used water that did not meet the requirements with the physical condition of the water were 46 (35.4%) smaller than those who met the requirements of 84 (64.6%). It is known that from 130 respondents, the microbiological quality of clean water was 54 (41.5%) less good than the good microbiological quality of clean water, which was 76 (58.5%). Sources of drinking water, it is known that out of 130 respondents, 61 (46.9%) received drinking water sources that did not meet the requirements, compared to 69 (53.1%) who received fulfilling requirements. Drinking water treatment found that out of 130 respondents, 48 ​​(36.9%) did not process drinking water, which was smaller than those who did process, namely 82 (63.1%). There is a significant relationship between the physical condition of water, the microbiological quality of drinking water, sources of drinking water, and drinking water treatment to the incidence of stunting in the working area of ​​the Tanjung Agung Health Center, Muara Enim Regency, 2023 with a p value of 0.000.